Pengembangan Kapasitas Kelompok Tani Tunas Makmur Dalam Pengelolaan Produk Nanas Di Kelurahan Sungai Pakning Kabupaten Bengkalis - Zatri Erlia; Dadang Mashur (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This research was conducted because Sungai Pakning Village, Bengkalis Regency, was one of the areas that experienced land and forest fires that occurred in Riau Province in 2015. So far, peatland management has often failed, both by the government and companies. One of their failures is that they only focus on land restoration and ignore community empowerment. With the independent peat village program created by PT. Pertamina RU II Production, Sungai Pakning, Bengkalis Regency. Among the independent peat village programs, there is an environmental conservation program which has become the center of attention for environmental observers, namely the development of peat forests to manage pineapple products. This research aims to determine the capacity development of the Tunas Makmur Farmer group in managing pineapple products and to find out what are the supporting factors for capacity development in the Tunas Makmur Farmer group in Sungai Pakning, Bengkalis Regency. This research was conducted using a qualitative descriptive method. Data was obtained through interviews and field observations. The results of this research show that the capacity development measure according to Ilato has demonstrated good capacity in aspects of organizational structure, decision making processes, work procedures and mechanisms and inter-organizational relationships. Good capacity development is supported by 1) facilities and infrastructure, which are being developed continuously, 2) good cooperation between various parties or institutions involved in developing the capacity of the Tunas Makmur Farmers Group.